Critiquing Capitalism Today New Ways to Read Marx - Pitts, Frederick Harry (Marx, Engels, and Marxisms,, 2018)
This book critically introduces and compares two of the most compelling contemporary schools of Marxist thought: the German Neue Marx-Lekture, or New Reading of Marx, and Italian postoperaismo. In so doing, it radically updates our understanding of the key categories of Marx's critique of political economy- including value, money, labour, class and crisis- in light of new and exciting theoretical developments. The New Reading of Marx reevaluates Marx's Capital in the shadow of the first-generation Frankfurt School, finding an increasing uptake in the Anglophone world. Postoperaismo reconceptualises Marx's work in the wake of the Grundrisse, its theories of immaterial labour and capitalist crisis finding growing favour beyond the radical fringe via recent bestsellers like Paul Mason's Postcapitalism. Drawing on the first to engage in a pathbreaking critique of the second at a time of peak interest in its optimistic prospectus, the book brings into critical dialogue important modern thinkers such as Michael Heinrich, Werner Bonefeld, and Antonio Negri. In so doing, Critiquing Capitalism Today serves as both an introduction to each of these radical reinterpretations of Marx's critique of political economy, and a contribution to continuing debates within and between these and other strands of contemporary Marxism. Advancing knowledge in the field by bridging recent scholarship with older material, including the works of Marx himself, Theodor Adorno and Alfred Sohn-Rethel, it relates theoretical disputes with their historical context in capitalist society itself, keeping an empirical focus that clarifies complex conceptual material for readers new to these cutting-edge currents of critical thought. .